The Influence of Creativity, Price And Product Quality On Consumer Satisfaction in The Bamboo Weaving Craft Business in Loyok Village - Nurlaili, Nurlaili; Fahrurrozi, Muh.; Zain, Rohaeniyah (JMET: Journal of Management Entrepreneurship and Tourism, 2024)
This research aims to examine the effect of creativity (X1), price (X2) and product quality (X3) partially and simultaneously on consumer satisfaction in the Bamboo woven craft business in Loyok village. This study used a quantitative approach with 90 research subjects. The data collection techniques and instruments used are observation, questionnaires (questionnaires) and documentation. The data from this study were tested using classical assumption tests, multiple linear regression analysis, t tests (partial) and f tests (simultaneous), as for the analytical techniques used, namely quantitative descriptive. The results of this study showed that the creativity variable had a positive and significant effect as much as 0.038, price had a positive and significant effect as much as 0.000 and product quality had a positive and significant effect as much as 0.000. Thus, it can be stated that partially the independent variable affects consumer satisfaction in the bamboo weaving craft business in Loyok Village, because the significant value is < 0.05. The independent variable simultaneously had a positive and significant influence on the dependent variable with a significant value of 0.000, so it was proven that simultaneously the variables of creativity, price and product quality affected consumer satisfaction in the bamboo woven craft business in Loyok Village with a strong influence of 61% while 39% was influenced by other variables outside this study.